New results on betting strategies, market selection, and the role of luck - Giulio Bottazzi; Daniele Giachini (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2018)
We consider a repeated betting market populated by two agents who wage on a binary event according to generic betting strategies. We derive new simple criteria to establish the relative wealth of the two agents in the long run, only based on the odds they believe fair and how much they would bet when the odds are equal to the ones the other agent believes fair. Using our criteria, we show that for a large class of betting strategies it is generically possible that the ultimate winner is only decided by luck. As an example, we apply our conditions to the case of CRRA betting.
Keywords: C60; D53; G11; G12; 330; Bounded Rationality; Betting Strategies; Market Selection; Recurrent Processes; Luck